Setting Time Dan Kuat Tekan Beton Pofa Dengan Tambahan Silica Fume Di Air Gambut - Ines Junita Sinuhaji; Iskandar Romey Sitompul; Monita Olivia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
As a province with the largest area of oil palm plantations in Indonesia, oil palm production in Riau continues to increase. When palm oil production increases, the residual waste of production also increases and has not been optimally utilized. This research aims to analyze characteristics of POFA (Palm Oil Fuel Ash) concrete by using additive silica fume with PCC (Portland Cement Composite) concrete as control. POFA is used as a partially substitute material of cement volume with variations 0% and 20%, which silica fume as addition material has constant levels in 10% of cement volume. In this research, the compressive strength and setting time of the concrete were tested. All variations were made and passed the curing stage for 28 days in plain water. The compressive strength test was carried using a cylindrical mold measuring 105 X 210 mm, while the setting time testing was carried out separately using the vicat tool. After the curing process, the specimens were immersed in peat water with immersion variations, namely 0.7, and 28 days. Setting time of PCC concrete is the longest binding time compared to other variations, in this research there are three variations. The final binding time of 145 minutes and the fastest final binding time, namely the variation with POFA 20% with the final binding time of 96 minutes. Concrete compressive strength was tested mechanically at 0, 7, and 28 days of peat water, while setting time was tested separately. The compressive strength plan is 20 MPa and peat water as immersion water of concrete has a pH 4.0-5.0. The results shows that the compressive strength of POFA variation concrete was higher than control concrete at 0 days of immersion with the highest compressive strength value at POFA 0% of 25,84 MPa. At 28 days of immersion, POFA 0% with silica fume was higher than the control. Increase level of POFA in mixture decrease the compressive strength to 21,18%. The lowest compressive strength than the control at POFA 20% of 25,76 MPa at 28 days. Based on the results of the test, it is concluded that the use of POFA affects the results of compressive strength and setting time. The results of the compressive strength test showed that more POFA in the concrete, the compressive strength tended to decrease at age of 0, 7, and 28 days. In testing the setting time, POFA has the effect of shortening the initial setting time and the final setting time. More levels of POFA decreased the setting time in this study. Keywords : Palm Oil Fuel ASh, Silica fume, PCC, Peat Water, Setting Time, Compressive Strength.